2014
DOI: 10.1364/ao.53.006435
|View full text |Cite
|
Sign up to set email alerts
|

Security analysis of phase-only DRPE based on known-plaintext attack using multiple known plaintext–ciphertext pairs

Abstract: Classical double-random phase encoding (C-DRPE) is an optical symmetric-key encryption technique. C-DRPE is reported to be vulnerable to a known-plaintext attack (KPA) that uses a phase retrieval algorithm. However, although phase-only DRPE (PO-DRPE) is reported to be more resistant to KPAs than C-DRPE, it is not obvious yet that PO-DRPE is sufficiently resistant to a KPA under any condition, because the vulnerability to KPA varies depending on various factors, such as the number of the known plaintext-ciphert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Therefore, the resistance to brute-force attacks of this architecture is analogous to the one appearing in [24]. Otherwise, the security will be compromised, like in other conventional systems [11][12][13][14][15][16][17][18], if an intruder has access to a subset of images belonging to the cyphertext and the optical parameters sent by different transmission channels as discussed in [24,25]. Consequently, this system is more secure than conventional holographic systems.…”
Section: Simulated and Experimental Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the resistance to brute-force attacks of this architecture is analogous to the one appearing in [24]. Otherwise, the security will be compromised, like in other conventional systems [11][12][13][14][15][16][17][18], if an intruder has access to a subset of images belonging to the cyphertext and the optical parameters sent by different transmission channels as discussed in [24,25]. Consequently, this system is more secure than conventional holographic systems.…”
Section: Simulated and Experimental Resultsmentioning
confidence: 97%
“…Numerous linear versions of this architecture have been presented in the fractional Fourier domain and Fresnel domain [3][4][5][6][7][8][9][10]. Nevertheless, it has been reported that some of these schemes are unsecure; some cryptoanalysis strategies have shown that any inherently linear optical encryption system is vulnerable [11][12][13][14][15][16][17][18]. Thus, optical encoding-decoding architectures overcoming this weakness, without losing confidence level, are valuable [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In a KPA attack, an adversary attempts to obtain some known plaintext-ciphertext pairs to hack them for concluding a cryptographic key used [41] [42]. An adversary prevails if a KPA attack results in concluding the cryptographic key used.…”
Section: B Known-plaintext Analysis (Kpa)mentioning
confidence: 99%
“…Despite the fact that a plurality of attacks have been designed to break DRPE systems [23][24][25][26][27][28][29][30], different approaches were suggested to improved security in DRPE. For instance, it has been demonstrated that quantum encryption systems that works with few photons are very secure [31,32].…”
Section: Encryption and Validationmentioning
confidence: 99%
“…Consequently, additional improvements with optical security techniques [16][17][18][19][20][21][22] could be adapted to be used with focused beams. To avoid conventional attacks against the information encrypted in the longitudinal component [23][24][25][26][27][28][29][30], the use of quantum imaging techniques is suggested [31][32][33].…”
Section: Introductionmentioning
confidence: 99%